Clarice Lispector - Weltliteratur? - Meyer-Krentler, Leonie (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2021)
It has only been in the 21st century that the literary oeuvre of the Brazilian author Clarice Lispector (1920-1977) has received international recognition, after being repeatedly forgotten in the past. This volume traces its belated transformation into world literature using specific materials from the history of Lispector's translation and reception, providing a new perspective on the problems of canonization in the field of world literature.